Role of Professional Service Quality and Communication Effectiveness in Predicting Relationship Commitment among Professional-Client in Lawyer Services - Abrar, Muhammad; Shabbir, Rizwan; Bashir, Mohsin; Saqib, Shahnawaz; Raza, Ahmed (International Review of Management and Marketing, 2020)
Globally, judicial sector regarding its relationship commitment has been discussed in few studies. In South-Asian context, service sector has been explored mostly with commercial industries like banks, restaurants and academic. However, professional industries like lawyers, doctors and brokers have rarely investigated by marketers to understand its relationship commitment with their clients considering their core antecedents. In such service industries, technical and functional service quality attributes along with communication effectives enhance client's satisfaction. Moreover, it examined trust and relationship quality of service provider that impact client-lawyer relationship commitment. Structured questionnaire was designed for collecting a sample of 220 clients who had/have encountered civil cases at district bar Faisalabad, Pakistan. Results of structured equation model shows that professional service quality and communication effectiveness promote relationship commitment among clients and professional lawyers. Also relationship quality mediates the relationship of service quality, communication effectiveness and relationship commitment. Limitations and future research directions are also discussed. Keywords: Relationship Commitment, Professional Service Quality, Relationship Quality, Communication effectiveness, professional services JEL Classifications: M310, M130 DOI: https://doi.org/10.32479/irmm.9387